Australia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper reviews how Australia's economy has adapted to a flexible Australian Dollar. The paper provides a background on the float and the initial policy challenges. It discusses the main elements of the Future Fund proposal, and estimates how much Australia and other countries in the Asia-Pacific region would gain from greater financial integration. The results suggest that these welfare gains are large, giving an argument in favor of a progressive capital account liberalization across the region, once the needed supporting measures are in place.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet